Performance Evaluation of Fiber Optic versus Copper Cable Networks: A Comparative Study - Muhammad Bitrayoga; Evan Haviana; Jeffrey Payung Langi; Sulastri Kakaly; Apriani Riyanti (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
This study presents a comparative performance evaluation of Fiber Ethernet and copper Ethernet (Cat6) using a controlled testbed to quantify differences in throughput and Quality of Service (QoS). Identical endpoints are connected through a managed switch, and the physical medium is alternated between a fiber link and a Cat6 link. Traffic is generated under TCP and UDP at three utilization levels (10%, 50%, and 90%) and three distance conditions (10 m, 50 m, and 90–100 m for Cat6). The evaluation uses application-level and interface-level measurements, including TCP/UDP throughput, round-trip latency, jitter, packet loss, and reliability counters such as CRC/FCS errors and TCP retransmissions. Results show that both media can achieve near line-rate throughput at short distance and low load, but fiber exhibits consistently lower latency and jitter and near-zero loss across conditions. As utilization increases, Cat6 displays larger variability in delay and a higher tendency toward UDP loss, indicating reduced timing stability under stress. At longer copper runs (90–100 m), the gap widens: Cat6 shows higher jitter and loss and increased error-related counters, while fiber remains stable. These findings suggest that the main advantage of fiber is not only peak capacity but also QoS predictability and link integrity, which are critical for real-time and high-utilization services. The study provides practical guidance for selecting media in campus and building networks where distance, load, and service requirements must be balanced. Future work will include electromagnetic-noise trials, different switch/NIC models, and statistical tests to validate effect sizes across repetitions in diverse building environments